Analisis dan Implementasi ERP pada Modul Point of Sale Studi Kasus Toko Tas Apidah - Lailia Cahya Putri; Suhendi Suhendi (Jurnal Informatika Terpadu, 2021)
At this time, the role of technology in Micro, Small, and Medium Enterprises (MSME) business activities is significant in supporting one of the success factors for entrepreneurs. One of them is the role of technology in incorporating data into the system in MSME business activities. Apidah's Bag Store is one of the players in the MSME business that sells different kinds of bags. The store has been operating since 2008 and already has a Jakarta branch. Based on the results of an interview with the owner of the Apidah Bag Store, he claimed that it was not reported in the book for the management of products. So the issue that may arise is the lack of a documented special sales report. The Apidah Bag Store does not have a goods management system, it is difficult for the store to know what products are still available in the store, and the profit that has been earned is also challenging to understand. One type of data integration system that is carried out is such as the use of the Odoo application to input data on products in the Apidah Bag Store. The Odoo software is an open-source, modern, and full Enterprise Resource Planning (ERP) application. In this analysis, the Point of Sale (POS) module is the Odoo program used. In the processing of purchase transaction details, sales, and transaction reporting, POS is used to support business managers or business owners. By going through multiple phases, the author implements the Odoo application at the Apidah Bag Shop. Starting from problem identification, preliminary research, review, system design, implementation, testing using black-box and UAT methods to outcomes of assessment and enhancement. At the Apidah Bag Shop, the introduction of the goods management system has been successfully carried out until the reporting stage on items that come out every day. Certain items are still unsuccessful, however, such as shifting currency and using businesses in the program.